2009
DOI: 10.1093/biolreprod/81.s1.349
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Novel Oocyte-Specific Gene Encoding an F-Box Protein in Rainbow Trout (Oncorhynchus mykiss).

Abstract: Background: Oocyte-specific genes play critical roles in oogenesis, folliculogenesis and early embryonic development. The objectives of this study were to characterize the expression of a novel oocyte-specific gene encoding an F-box protein during ovarian development in rainbow trout, and identify its potential interacting partners in rainbow trout oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Electrophoresis and transfer were performed according to a previous study with minor modifications [45]. HEK293 cell were harvested with Pierce IP Lysis Buffer (Thermo Fisher Scientific, Waltham, MA), and 10 μl of cell lysate were mixed with an equal volume of Laemmli sample buffer (Bio-Rad Laboratories, Hercules, CA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Electrophoresis and transfer were performed according to a previous study with minor modifications [45]. HEK293 cell were harvested with Pierce IP Lysis Buffer (Thermo Fisher Scientific, Waltham, MA), and 10 μl of cell lysate were mixed with an equal volume of Laemmli sample buffer (Bio-Rad Laboratories, Hercules, CA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Electrophoresis and transfer were performed according to a previous study with minor modifications [45].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…These data indicate that Figla plays a critical role in activation of oocyte development and repression of testis development to maintain the sex-specific germ cell development. In cattle, Figla shows similar expression profile as in other mammals, which is restricted to gonadal tissues and appears as early as primordial follicle stage (Tripurani, et al 2013) were decreased after embryonic genome activation suggesting miRNA212 might be a maternal origin factor involved in maternal transcript degradation during the MZT.…”
Section: Figla: Factor In Germline Alphamentioning
confidence: 58%
“…and Figla 3'UTR, and studies on in vitro cultured (IVC) bovine embryos revealed that miRNA212 mimic inhibits Figla protein expression (Tripurani, et al 2013). These studies indicate that Figla is a critical factor for follicular and embryo development and miRNA212 is a potential post-transcriptional regulator of Figla during the MZT in cattle.…”
Section: Figla: Factor In Germline Alphamentioning
confidence: 83%
See 1 more Smart Citation